Batman comic chapter books Scarecrow's panic plot - Beatty, Scott (North Mankato, Minnesota Stone Arch Books, a Capstone imprint, 2015)
After he falls into Scarecrow's trap, Batman is fitted with a helmet that slowly releases a fear-inducing gas, leaving him terrified of everything around him--even Robin and Nightwing, who are trying to save him
A gift from book Africa
Comic strips
1 2 13 15
Keywords: Batman (Fictitious character) -- Comic books, strips, etc; Superheroes -- Fiction